SOCIAL EXPECTATIONS OF AI AND THE PERFORMATIVITY OF ETHICS - Kerr, Aphra; Barry, Marguerite; Kelleher, John (AoIR Selected Papers of Internet Research, 2020)
This article draws on the sociology of expectations to examine the construction of expectations of ‘ethical AI’ and considers the implications of these expectations for communication governance. We first analyse a range of public documents in the EU, the UK and Ireland to identify the key actors, mechanisms and issues which structure societal expectations around AI and an emerging discourse on ethics. We then explore expectations of AI and ethics through a survey of members of the public. We conclude that discourses of ‘ethical AI’ are generically performative, but to become more effective in practice we need to acknowledge the limitations of contemporary AI and the requirement for extensive human labour to deploy AI in specific societal contexts. An effective ethics of AI requires domain appropriate AI tools, updated professional practices, dignified places of work and robust regulatory and accountability frameworks.